CHALLENGES IN PROVIDING QUALITATIVE LEGAL EDUCATION IN THE CONTEXT OF COVID-19: EXPERIENCE OF RĪGA STRADINS UNIVERSITY - Vilks, Andrejs; Kipane, Aldona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The spreading of COVID-19 since March 2020 has had a profound and irreversible impact on all spheres of life around the world. The long-term impact of the pandemic with unpredictable consequences will also be observed in the field of education. The aim of the article is to analyse the potential impact of COVID-19 on the providing of qualitative legal education. Full-fledged assurance of the qualitative education is linked to common conditions for acquiring of knowledge, skills and competences. There are certain specifics in obtaining legal education, especially higher education. It is related to a combination of circumstances that are relevant to the specific knowledge, skills and competences to be acquired by lawyers and legal assistants. In 2020 a new standard for the legal profession was approved, which not only defines new qualitative requirements for the relevant profession, but also determines the need to make adjustments in the relevant study programs. The process of implementing and performing qualitative legal education in the current circumstances is being transformed in line with the international and national regulatory frameworks in the context of management of COVID-19. As research methods descriptive, analytical and synthetic methods are used by the authors.